Poly((2‐alkylbenzo[1, 2, 3]triazole‐4, 7‐diyl)vinylene)s for organic solar cells. Issue 21 (24th July 2015) - Akpinar, Handan; Cevher, Şevki Can; Wei, Lang; Cirpan, Ali; Wong, Bryan M.; Venkataraman, Dhandapani; Lahti, Paul M.
ABSTRACT Poly((2‐Alkylbenzo[1, 2, 3]triazole‐4, 7‐diyl)vinylene)s (pBTzVs) synthesized by Stille coupling show different absorption spectra, solid‐state morphology, and photovoltaic performance, depending on straight‐chain versus branched‐chain (pBTzV12 and pBTzV20) pendant substitution. Periodic boundary condition density functional computations show limited alkyl pendant effects on isolated chain electronic properties; however, pendants could influence polymer backbone conjugative planarity and polymer solid film packing. The polymers are electronically ambipolar, with best performance by pBTzV12 with hole and electron transport mobilities of 4.86 × 10−6 and 1.96 × 10−6 cm2 V−1 s−1, respectively. pBTzV12 gives a smooth film morphology, whereas pBTzV20 gives a very different fibrillar morphology. For ITO/PEDOT:PSS/(1:1 w/w polymer:PC71BM)/LiF/Al devices, pBTzV12 gives power conversion efficiency (PCE) up to 2.87%, and pBTzV20 gives up to PCE = 1.40%; both have open‐circuit voltages of VOC = 0.6–0.7 V. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1539–1545